Measures of macroscopicity for quantum spin systems - Florian Fröwis; Wolfgang Dür (New Journal of Physics, 2012)
We investigate the notion of ‘macroscopicity’ in the case of quantum spin systems and provide two main results. Firstly, we motivate the quantum Fisher information as a measure of the macroscopicity of quantum states. Secondly, we make a comparison with the existing literature on this topic. We report on a hierarchy among the measures and we conclude that one should carefully distinguish between ‘macroscopic quantum states’ and ‘macroscopic superpositions’, which is a strict subclass of the former.